Anonymous addressing servers: a solution of failures in wireless mobile location service. (4th December 2009) - Alchaita, Mohammed; Alani, Omar
In this paper, a new Adaptive Centralised Location-Service (ACLS) routing protocol is presented, which tracks mobile node locations and recover the side effects of nodes mobility. In ACLS, some nodes consider themselves as servers serve other nodes according to their location and status in the network. The transmission is achieved by 'anonymous addressing' technique where the receivers decide on their own, whether they are the intended destination. Results indicate very good and impressive performance of the ACLS in terms of scalability with the number of nodes, speed and location update success rate.